Incidence of Acute Kidney Injury in Cases Presenting With Acute Gastroenteritis in a Tertiary Care Hospital - Balouch, Ali Raza; Afaq, Muhammad Farooq; Alam, Mazhar Faiz; Nasreen, Saima; Shaheen, Muhammad Arif; khan, Mahlaqa (Biological and Clinical Sciences Research Journal, 2025)
Acute kidney injury is a frequent and potentially serious complication of acute gastroenteritis, particularly in hospitalized patients. Dehydration, prolonged illness, and comorbid conditions such as diabetes mellitus can predispose patients to renal hypoperfusion and subsequent kidney injury. In Pakistan, limited local data exist regarding the burden of acute kidney injury among patients presenting with acute gastroenteritis in tertiary care settings. Objective: To determine the frequency of acute kidney injury among patients presenting with acute gastroenteritis in a tertiary care hospital. Methods: This descriptive cross-sectional study was conducted in the inpatient, Accident and Emergency, and Medicine departments of Bahawal Victoria Hospital, Bahawalpur, from December 2024 to April 2025. A total of 180 patients aged 14–60 years with a diagnosis of acute gastroenteritis were enrolled using non-probability consecutive sampling. Acute kidney injury was defined according to KDIGO criteria as an increase in serum creatinine of at least 0.4 mg/dL within 48 hours of admission. Demographic, clinical, and laboratory data were recorded. Data were analyzed using SPSS version 23. Frequencies and percentages were calculated for qualitative variables, and means and standard deviations were computed for quantitative variables. Stratification was performed to assess associations between acute kidney injury and selected variables, with p-values ≤ 0.05 considered statistically significant. Results: The mean age of the participants was 38.6 ± 11.2 years, with a male predominance (62.2%). Acute kidney injury was observed in 15.0% of patients presenting with acute gastroenteritis. A statistically significant association was found between acute kidney injury and the older age group (p = 0.018), diabetes mellitus (p = 0.009), duration of symptoms greater than three days (p = 0.021), and severe dehydration (p < 0.001). Gender was not associated with acute kidney injury (p = 0.298). Conclusion: Acute kidney injury is a common complication among patients hospitalized with acute gastroenteritis. Older age, diabetes mellitus, prolonged symptom duration, and severe dehydration are significant risk factors. Early identification and prompt management of dehydration may reduce the burden of acute kidney injury in such patients.